2007
DOI: 10.1007/s10895-007-0283-0
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Puerarin to Human Serum Albumin: A Spectroscopic Analysis and Molecular Docking

Abstract: Puerarin is a widely used compound in Chinese traditional medicine and exhibits many pharmacological activities. Binding of puerarin to human serum albumin (HSA) was investigated by ultraviolet absorbance, fluorescence, circular dichroism and molecular docking. Puerarin caused a static quenching of intrinsic fluorescence of HSA, the quenching data was analyzed by Stern-Volmer equation. There was one primary puerarin binding site on HSA with a binding constant of 4.12 x 10(4) M(-1) at 298 K. Thermodynamic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(53 citation statements)
references
References 33 publications
3
50
0
Order By: Relevance
“…[35,36]. In this study molecular docking simulation has been used to improve the understanding of the interaction of drug to HSA [37][38][39]. As shown in the Figure 11 …”
Section: Uv-visible Absorption Spectral Studymentioning
confidence: 99%
“…[35,36]. In this study molecular docking simulation has been used to improve the understanding of the interaction of drug to HSA [37][38][39]. As shown in the Figure 11 …”
Section: Uv-visible Absorption Spectral Studymentioning
confidence: 99%
“…The bonding provides specificity and stabilisation of binding between a and enzyme active site which consequently enhanced the binding affinity [38,39]. Other basic residues such as Pro 1154, Ile 1153, Val 1213, Ala 1254, Hoh 2087, Hoh 2067, Arg 171, and Gly 242 were observed in the vicinity of compound a, which suggested that a strong electrostatic interaction was also involved in the binding process [40].…”
Section: Molecular Docking Design and Optimisationmentioning
confidence: 97%
“…45 CD spectra of BSA exhibited two negative bands at 208 and 222 nm, characteristic of α-helix structure units of the protein. 46 CD spectra (200-260 nm) of BSA were recorded in the absence and presence, at different concentrations, of t-DCTN at 296, 303 and 310 K ( Figure 5). Upon increasing the t-DCTN concentration in the albumin solution, a small and a moderate decrease in the intensity at 208 and 222 nm, respectively, can be clearly observed.…”
Section: Thermodynamic Parameters and The Main Binding Force Between mentioning
confidence: 99%